2020
DOI: 10.3390/ijms21238955
|View full text |Cite
|
Sign up to set email alerts
|

Age, Diet and Epidermal Signaling Modulate Dermal Fibroblasts’ Adipogenic Potential

Abstract: The recognition of a distinct fat depot, the dermal white adipose tissue (dWAT), points out the complexity of the interaction among skin resident cells: keratinocytes, dermal fibroblasts (DFs) and adipocytes in response to physiological (diet, age) and pathological (injury) stimulations. dWAT has been recognized as a significant contributor to thermoregulation, hair cycle, immune response, wound healing and scarring. In this study, we examined age- and diet-related changes in dWAT modulation and DFs’ adipogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…Although the classic studies by Chase et al [ 6 ], in the 1950s, demonstrated the synchrony between dermal adipocytes and hair follicle cycling, it was the work of Wojciechowicz et al [ 7 ], focusing on adipocyte development in mouse dorsal skin, that firmly established the presence of adipocyte tissue within the dermis that the authors named the dermal white adipose tissue (dWAT). The dWAT is a type of white adipose tissue and, similar to other fat depots, its content is regulated by the diet and increases in an obesogenic environment in both young and old mice that are fed a high-fat diet (HFD) [ 8 , 9 ]. In old mice, an increase in dWAT, due to 8 weeks of HFD feeding, seems to compensate for age-related skin (fibroblast-rich dermis) thinning [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the classic studies by Chase et al [ 6 ], in the 1950s, demonstrated the synchrony between dermal adipocytes and hair follicle cycling, it was the work of Wojciechowicz et al [ 7 ], focusing on adipocyte development in mouse dorsal skin, that firmly established the presence of adipocyte tissue within the dermis that the authors named the dermal white adipose tissue (dWAT). The dWAT is a type of white adipose tissue and, similar to other fat depots, its content is regulated by the diet and increases in an obesogenic environment in both young and old mice that are fed a high-fat diet (HFD) [ 8 , 9 ]. In old mice, an increase in dWAT, due to 8 weeks of HFD feeding, seems to compensate for age-related skin (fibroblast-rich dermis) thinning [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also determined that mature adipocytes after skin injury undergo lipolysis to release fatty acids (FAs), which in turn stimulate macrophage infiltration, whereas post-lipolytic adipocytes change their identity to become myofibroblasts. Walendzik et al demonstrated that the migration of dermal fibroblasts (DFs) from skin explants collected from HFD mice is much more robust than that from mice fed a low-fat diet (LFD), regardless of animal age (young vs. old) [ 9 ]. Follow-up analysis of DFs isolated from the skin of young and old mice fed a low-fat diet (LFD) or HFD, revealed differences in their adipogenic potential, particularly related to animal age, with respect to Zfp423 (determinant of preadipocyte commitment) and Zfp521 (negative regulator of adipogenesis) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations